MENINGKATKAN KEMAMPUAN MENGIDENTIFIKASI STRUKTUR DAN UNSUR KEBAHASAAN TEKS CERITA FANTASI SISWA KELAS VII B SMP NEGERI 6 TABANAN - Ni Luh Nanik Puspadi (WACANA : MAJALAH ILMIAH TENTANG BAHASA, SASTRA DAN PEMBELAJARANNYA, 2022)
Learning to identify the structure and linguistic elements of fantasy story texts has been taught in class VII B State Junior High School 6 Tabanan according to the 2013 curriculum. the average obtained by students is still relatively low. This happens because of the inaccuracy of the learning method applied by the teacher when the learning process takes place. Teachers theorize more, so students feel bored and less interested in participating in learning. This study aims to describe students' abilities in identifying the structure and linguistic elements of fantasy story texts before and after applying the discovery learning method and improving learning outcomes obtained by class VII B students of State Junior High School 6 Tabanan in the 2021/2022 academic year. Data collection methods used, namely the method of observation, test method and method of recording documents. Observation method was used to obtain data about students' attitudes and behavior. The test method is used to determine the students' ability to identify the structure and linguistic elements of fantasy story texts. The data analysis method used is descriptive analysis method. Based on the data analysis that has been carried out, the results obtained are, the average value of students in the pre-cycle is 65.00 then in the first cycle it increases to 73.82 with a percentage increase of 14.76% and in the second cycle it increases again to 84.41 with a percentage increase of 14.76%. an increase of 15.51%. Thus, if it is connected with the action hypothesis, the ability to identify the structure and linguistic elements of fantasy story texts by applying the discovery learning method for class VII B students of State Junior High School 6 Tabanan in the 2021/2022 school year increases significantly. Key words: Identifying, Structure and Language Elements, Fantasy Story Text, Discovery Learning Method